Bone marrow transplantation for severe aplastic anemia: a randomized controlled study of conditioning regimens - Champlin, Richard E. (American Society of Hematology, 2007)
The addition of antithymocyte globulin (ATG) to a regimen of high-dose cyclophosphamide has been advocated to enhance engraftment after allogeneic bone marrow transplantation (BMT) for severe aplastic anemia (SAA). In a prospective clinical trial, 134 patients were randomly assigned to receive cyclophosphamide alone or in combination with ATG. All patients received T-cell–replete bone marrow from an HLA-matched sibling. With a median follow-up of 6 years, the 5-year probabilities of survival were 74% for the cyclophosphamide alone group and 80% for the cyclophosphamide plus ATG group (P = .44). Graft failure and graft-versus-host disease (GVHD) rates were similar in both groups. With the survival rates achieved, this study is not adequately powered to detect significant differences between the 2 treatment groups. In conclusion, the results of allogeneic BMT for SAA have improved over time related to advances in supportive care. The addition of ATG to the preparative regimen did not significantly improve the outcome.